The effect of new drug pricing systems and new reimbursement guidelines on pharmaceutical expenditures and prescribing behavior among hypertensive patients in Korea. Issue 5 (May 2015) - Cho, Mee-Hyun; Yoo, Ki-Bong; Lee, Hoo-Yeon; Lee, Kwang-Sig; Kwon, Jeoung A; Han, Kyu-Tae; Kim, Jae-Hyun; Park, Eun-Cheol
Highlights: We assessed the effects of the new drug pricing system and the new guideline on pharmaceutical expenditure and prescribing behavior. Antihypertensive drug costs per patient and antihypertensive drug costs per prescribed day decreased. There was little sign to increase or changes of the quantity of drugs. Both the cost of original drugs and the number of original drugs prescribed decreased significantly. Both the pricing policy reform and the prescription and reimbursement guidelines were reducing pharmaceutical expenditure without increasing quantities. Abstract: Objective: The purpose of this study was to determine the effects of a new drug-pricing system (January 2012) and new prescription and reimbursement guidelines (January 2013) on hypertension-related pharmaceutical expenditures and prescribing behaviors in Korea. Methods: In all, 11, 298 clinics and 2, 667, 132 patients with hypertension were included in our study. As dependent variables, we used the drug cost per patient, drug cost per prescribed day, number of drugs per prescription, number of prescribed days per visit, number of visits, number of original (vs. generic) drugs prescribed, and the percentage of original drug cost. Clinic characteristics and patients' age and sex were used as independent variables. Multi-level mixed-effect regression models were used. Results: The drug cost per patient decreased by −1446 KRW (−7.4%; p < 0.001) in Q4 2012 and by −1833 (−9.3%; p < 0.001) in Q2 2013 compared with Q4 2011. Number of drugs per prescription decreased significantly. The percentage of original drug cost and the number of original drugs also declined. Conclusion: Reforms to the drug pricing policy and the new guidelines may reduce pharmaceutical expenditures without increasing number of drugs per prescription and the number of original drug used. Policy makers should consider the comprehensive effects of implementing new policies on both drug prices and consumption.